Gross Morphometric Study on Postnatal Development of Adrenal Gland in Gohilwadi Goat (Capra Hircus) - Kumar, Vishnudeo; Sharma, Anil (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A study was conducted on the adrenal gland of 20 Gohilwadi goats (Capra hircus), age ranging from day old to adult. Animals were divided in three age groups, viz., group-I (day old to 1 month), group-II (1 to 6 months) and group-III (above 6 months). The different gross and biometric parameters, viz., weight, length, width and thickness of both left and right adrenal gland were recorded. The left adrenal gland was roughly oval elongated and right was roughly triangular in shape in all the age groups. Different biometric parameters of adrenal gland increased significantly (P0.05) in various gross and biometric observations between left and right adrenal gland within the same group.
Keywords: Adrenal gland; Goat; Morphometry; Postnatal development